2013
DOI: 10.1016/j.intimp.2013.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two serine proteases from Bothrops pirajai snake venom on the complement system and the inflammatory response

Abstract: The present study aimed to evaluate the effects of two serine proteases from Bothrops pirajai snake venom, named BpirSP27 and BpirSP41, on the complement system and the inflammatory response. The effects of these enzymes on the human complement system were assessed by kinetic hemolytic assays, evaluating the hemolysis promoted by the classical/lectin (CP/LP) and alternative (AP) pathways after incubation of normal human serum with the serine proteases. The results suggested that these enzymes were able to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 43 publications
2
31
0
12
Order By: Relevance
“…Complement activation by an animal's toxin and its role in the envenomation remains poorly studied, but has been described for some snake venoms belonging to the Elapidae and Viperidae families [27][33], [19].…”
Section: Discussionmentioning
confidence: 99%
“…Complement activation by an animal's toxin and its role in the envenomation remains poorly studied, but has been described for some snake venoms belonging to the Elapidae and Viperidae families [27][33], [19].…”
Section: Discussionmentioning
confidence: 99%
“…injection and releasing important inflammatory mediators such as the eicosanoids PGD 2 , PGE 2 , TXA 2 , LTB 4 , the cytokines TNF-α, IL-6, IL-10, and the chemokine CCL-2 [52]. These inflammatory effects are most commonly related to phospholipases A 2 and metalloproteinases [72,73], although other classes of enzymes may also contribute to these responses [49].…”
Section: Discussionmentioning
confidence: 99%
“…All SVSPs identified to date present a catalytic triad comprising histidine (His), aspartate (Asp), and serine (Ser), essential for their enzyme activity [2,5]. Recent studies strongly suggested that serine proteases BpirSP27 and BpirSP41, purified from Bothrops pirajai (Bpir), were able to activate the complement system, potentially inducing edema under experimental conditions, and may include proinflammatory features, as well as being significantly inhibited by nonsteroidal anti-inflammatory drugs [6,7,8]. Other SVSPs purified from Bothrops alternatus , Bothrops mooeni [9], Trimeresurus elegans , and Trimeresurus jerdonni venom revealed the ability to release kinin, as well as fibrinolytic and edematogenic activities [10].…”
Section: Introductionmentioning
confidence: 99%
“…The most stable product derived from the arachidonic pathway is prostaglandin E2 (PGE2). In addition, the presence of cell-surface receptors represents another essential feature of cPLA2,which stimulates the signaling pathways associated with the activation of protein kinases and the production of reactive oxygen species (ROS) [6,16,24]. …”
Section: Introductionmentioning
confidence: 99%